Pengaruh Literasi Keuangan Digital dan E-Commerce Terhadap Perilaku Doom Spending di Kalangan Generasi Z Universitas Negeri Jakarta - Salma Zahra Andriani; Siti Nurjanah; Saparuddin Mukhtar (Indo Publishing, 2026)
This study aims to determine the influence of digital financial literacy and e-commerce on doom spending behavior among Generation Z at Jakarta State University. The population in this study were students as a representation of Generation Z in the campus environment. The sample of this study were active students at Jakarta State University with the sampling technique used was purposive sampling. The method used in this study was a quantitative method with multiple regression analysis. The results of the study found that the digital financial literacy variable was proven to have a positive and significant influence on doom spending behavior. This shows that respondents' understanding of digital financial instruments and the ease of online transactions does not necessarily make them wiser in refraining from impulsive shopping in stressful situations. On the contrary, mastery of financial technology actually becomes a means that makes it easier for respondents to make quick spending to relieve anxiety, so that the higher the digital financial literacy possessed, the tendency to doom spending also tends to increase. The e-commerce variable has a positive and significant influence as the main driving factor in doom spending behavior. The presence of online shopping platforms with various features of easy access, attractive promotions, and transaction speed has a very large impact in triggering unplanned spending. The practical nature of e-commerce has become a primary outlet for respondents to escape negative feelings or the stress of bad news through shopping, making it the most dominant factor in explaining why doom spending behavior occurs among the subjects of this study.